The 2025 Pilkada Phenomenon Preparation, Candidates, and Political Dynamics in the Election - Maruci, Cici (Sultan Agung Notary Law Review, 2025)
This study uses qualitative methods to understand the dynamics of political tensions after the 2024 elections in maintaining democratic stability in Indonesia. The type of research chosen is a case study, which allows for in-depth exploration of the specific context and complexity of the post-election political situation. Regional Head Elections (Pilkada) are a means of implementing people's sovereignty in the regions. This is a development in the governance system in Indonesia. In the Indonesian government, one of the principles known is the principle of autonomy, which means that there is freedom for the Regional Government to regulate its own region. Pilkada is a means to elect regional heads and people's representatives in the DPRD, where they are directly elected by the people in their regions. Thus, the legitimacy of the position of Regional Heads and DPRD Members becomes more representative, if this Pilkada is carried out democratically and in accordance with applicable procedures based on laws and regulations. The principles that must be met by election organizers as per the International IDEA standards have also been formulated in the Election Law, stated in Article 3 of Law 7/2017, election organizers in carrying out the election stages must meet the principles of independence, honesty, fairness, law, order, openness, proportionality, professionalism, accountability, effectiveness, and efficiency.